Urgensi Pembaharuan Asas Legalitas Dalam KUHP Nasional - Juniawan, Arbi; Susanti, Emilia; Dewi, Erna (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
The reform of Indonesian criminal law through the new Criminal Code (Law No. 1 of 2023) introduces the concept of "living law in society," allowing the application of customary norms to balance legal certainty and social justice. Although it aims to accommodate cultural diversity, its implementation faces challenges, such as the definition of living law, difficulties in formulating crimes, and potential conflicts between customary law and formal law. This legal uncertainty can reduce public trust in the justice system. Therefore, intensive socialization and legal education for the community are essential, supported by the participation of academics and legal practitioners to ensure that human rights protection remains a priority. This step is expected to create a fair, effective, and inclusive criminal justice system